ANALGESIC, ANTI-INFLAMMATORY AND WOUND HEALING PROPERTIES OF ARECANUT, ARECA CATECHU L. : A REVIEW - Bhat Sarpangala, Keshava; Ashwin, *Devasya; Sarpangala, Mythri (International Journal of Ayurveda and Pharma Research, 2017)
Wounds are unavoidable and most frequent injuries that occur during the daily activities of man and his livestock. Unless the wounds are cured properly in time it may lead to several other complications. In modern day medicine, antibiotic treatments are generally advocated for such injuries. But, due to several side effects and development of resistance by certain bacterial strains against such antibiotics there is a need to explore some alternative and effective therapeutics of plant origin which are cheap and relatively safe for mankind. Already several folklore medicines of plant origin are in vogue in several villages. Arecanut, Areca catechu L. is one such medicinal palm, the nuts of which are being used for the treatment of wounds since many years. The analgesic, anti-inflammatory and wound healing properties of arecanut are now authenticated by several scientific studies. The present paper aims at compiling such literature on this medicinal palm which is abundantly grown in several south and southeast Asian countries.